2019
DOI: 10.3390/ijerph16183253
|View full text |Cite
|
Sign up to set email alerts
|

A Correlational Analysis of the Relationships among Intolerance of Uncertainty, Anxiety Sensitivity, Subjective Sleep Quality, and Insomnia Symptoms

Abstract: In this study, we used structural equation modeling to investigate the interplay among Intolerance of Uncertainty (IU), Anxiety Sensitivity (AS), and sleep problems. Three hundred undergraduate students completed the Intolerance of Uncertainty Scale, the Intolerance of Uncertainty Inventory, the Anxiety Sensitivity Index, the Beck Depression Inventory, the State-Trait Anxiety Inventory, the Pittsburgh Sleep Quality Index and the Insomnia Severity Index. 68% and 40% of the students reported poor sleep quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 58 publications
4
42
0
5
Order By: Relevance
“…Worry and ruminating thoughts provoke cognitive arousal and may disturb cortisol homeostasis, resulting in poorer sleep. Such associations have previously been reported under similar circumstances ( 41 ). Furthermore, there is existing evidence that loneliness and poor sleep have a bi-directional relationship ( 42 ).…”
Section: Discussionsupporting
confidence: 88%
“…Worry and ruminating thoughts provoke cognitive arousal and may disturb cortisol homeostasis, resulting in poorer sleep. Such associations have previously been reported under similar circumstances ( 41 ). Furthermore, there is existing evidence that loneliness and poor sleep have a bi-directional relationship ( 42 ).…”
Section: Discussionsupporting
confidence: 88%
“…Ruminating thoughts provoking cognitive arousal and unpleasant physical reactions also hinder sleep promotion. This is in line with previous findings (Lauriola et al, 2019) and may also explain the high AIS scores in those answering "I don't know" when asked if they, or someone else close to them, had contracted the virus, since this answer suggests uncertainty. In this study, COVID-19 worry was also associated with insomnia.…”
Section: Dear Editorsupporting
confidence: 91%
“…Sleep research has shown that stress uniquely predict poor sleep quality, while IU has been less studied with sleep problems [20]. Previous research has overlooked the role of cognitive dispositions that might exacerbate stress, thus contributing to the continuation of sleep problems [14]. Perceived uncertainty and IU might be such dispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Intolerance of uncertainty (IU) relates to the cognitive unacceptability of uncertainty and represents a dispositional characteristic from those people who are more likely to " nd ambiguity stressful and upsetting, believe uncertainty is negative and should be avoided, and have di culty functioning in uncertain situations" [13,14]. Although uncertainty is pervasive and inherent in people's daily life, individuals who have high degree of perceived uncertainty or who are high in IU experience might signi cantly impair their daily functioning [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation